Multi-objective Function Optimization of 2-RPU&2-SPS Parallel Mechanism Based on Adams - Wang, Chongshan; Li, Bin; Zhu, Jiaqi; Li, Qi; Zhang, Yuan (2021 6th IEEE International Conference on Advanced Robotics and Mechatronics (ICARM), 2021)
The 2-RPU&2-SPS four degree of freedom parallel mechanism is a mechanism with two-by-two symmetrical motion branch chains. Some design parameters of the mechanism can be changed within a certain range. These variable parameters have a certain influence on the design goal. How to choose variable parameter values in order to optimize the design goals. These problems can be solved through parametric design and optimization analysis. This article uses the parametric modeling and optimization analysis functions provided by Adams/View to establish a parametric model of the mechanism by creating four design variables, and the effective value of transmission efficiency index, driving speed stability, total kinetic energy and driving force is four Objective function, introduce weighting factor, transform multiple objective functions into a total objective function for mechanism optimization analysis.